Evaluation of antibiotic consumption using WHO -antimicrobial consumption tool and AWaRe classification - Julie Birdie Wahlang; Reuben P. Syiem; Chayna Sarkar; Nari M. Lyngdoh; Iadarilang Tiewsoh; Dhriti K. Brahma; Aitilutmon Surong; Arky J Langstieh (Journal of Family Medicine and Primary Care)
Introduction: Antimicrobial resistance is a public health concern with global ramifications. Antibiotic misuse and overuse, are rampant in our country but more alarming is the data on the use of antibiotics primarily because of lack of access is another threat. A majority of the data on drug sales and consumption in India comes from the private sector and is typically gathered from private commercial organization. Because data on antibiotic usage in India is rarely reported, the study’s objectives were to estimate antibiotic consumption in ICU patients and also to assess antibiotic usage trends using the WHO AWaRE classification. Materials and Methods: A prospective observational study was carried out in the ICU department for six months after obtaining institutional ethics committee approval (P14/2021/14). In-patient records and details on antibiotic prescriptions were collected from the day of admission until they were discharged from the intensive care unit. Data on antibiotic consumption were retrieved from the hospital pharmacy. Descriptive statistics such as frequency, percentages, and means were used to summarize the data. Microsoft Excel 2016 was used for all statistical analyses. Results: The results of the study showed that female patients (54%), made up a significant majority of those receiving antimicrobial treatment. The age group between 40–49 years (21.68%) was the most common for those receiving antimicrobial treatment. Surgical prophylaxis (37.34%) emerged as the most common indication. Among the different antimicrobials studied, ceftriaxone 1 gm (108.5 DDD) emerged as the most prescribed antimicrobial. The access group of antibiotics accounted for 55% of the total usage. Conclusion: Appropriate use of antibiotics is important to minimize the risk of adverse events and antimicrobial resistance.